Identifying Effective Enzyme Activity Targets for Recombinant Class I and Class II Collagenase for Successful Human Islet Isolation. Issue 1 (January 2016) - Balamurugan, Appakalai N.; Green, Michael L.; Breite, Andrew G.; Loganathan, Gopalakrishnan; Wilhelm, Joshua J.; Tweed, Benjamin; Vargova, Lenka; Lockridge, Amber; Kuriti, Manikya; Hughes, Michael G.; Williams, Stuart K.; Hering, Bernhard J.; et al.
Abstract : Background: Isolation following a good manufacturing practice-compliant, human islet product requires development of a robust islet isolation procedure where effective limits of key reagents are known. The enzymes used for islet isolation are critical but little is known about the doses of class I and class II collagenase required for successful islet isolation. Methods: We used a factorial approach to evaluate the effect of high and low target activities of recombinant class I (rC1) and class II (rC2) collagenase on human islet yield. Consequently, 4 different enzyme formulations with divergent C1:C2 collagenase mass ratios were assessed, each supplemented with the same dose of neutral protease. Both split pancreas and whole pancreas models were used to test enzyme targets (n = 20). Islet yield/g pancreas was compared with historical enzymes (n = 42). Results: Varying the Wunsch (rC2) and collagen degradation activity (CDA, rC1) target dose, and consequently the C1:C2 mass ratio, had no significant effect on tissue digestion. Digestions using higher doses of Wunsch and CDA resulted in comparable islet yields to those obtained with 60% and 50% of those activities, respectively. Factorial analysis revealed no significant main effect of Wunsch activity or CDA for any parameter measured. Aggregate results from 4 different collagenase formulations gave 44% higher islet yield (>5000 islet equivalents/g) in the body/tail of the pancreas (n = 12) when compared with those from the same segment using a standard natural collagenase/protease mixture (n = 6). Additionally, islet yields greater than 5000 islet equivalents/g pancreas were also obtained in whole human pancreas. Conclusions: A broader C1:C2 ratio can be used for human islet isolation than has been used in the past. Recombinant collagenase is an effective replacement for the natural enzyme and we have determined that high islet yield can be obtained even with low doses of rC1:rC2, which is beneficial for the survival of islets.